THE IMPACT OF TOTAL VIDEOS AND TOTAL VIEWS ON SUPER CHAT EARNINGS FOR VIRTUAL YOUTUBERS IN PHILIPPINES AND THAILAND: THE ROLE OF TOTAL SUBSCRIBERS AS AN INTERVENING VARIABLE - Wily Mohammad; Nabilla Ryca Maulidiyah (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
This quantitative research employs Partial Least Squares Structural Equation Modeling (PLS SEM) using Smart PLS 4 to analyze the financial dynamics of VTuber YouTube channels in the Philippines and Thailand. The study utilized purposive sampling, comprising 81 channel samples, to explore the relationships between key variables. This research found that Total Subscribers has positive and significant effect to Super Chat Earnings, Total Views has negative but not significant effect to Super Chat Earnings, Total Videos has negative and significant effect to Super Chat Earnings, Total Videos has negative and significant effect to Super Chat Earnings through Total Subscribers, Total Views has positive and significant effect to Super Chat Earnings through Total Subscribers, Total Videos has negative but not significant effect to Total Subscribers, and Total Views has negative and significant effect to Total Subscribers of Philippines and Thailand VTuber YouTube channels.